Behaviors and Needs of Thai and Foreign Wellness Tourists in Upper North of Thailand - Krajangchom, Sansanee; Sangkakorn, Korawan (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2020)
This research aimed to: 1) study the travel behaviors of wellness tourists 2) study tourism needs of wellness tourists in upper north of Thailand and 3) propose guidance in responding to the wellness tourism needs of Thai and foreign tourists in the upper north of Thailand. The samples were 449 Thai tourists and 643 foreign tourist, and questionnaire was used as a tool to collect data. The statistics used in data analysis were frequency, percentage, standard deviation and weighted mean score. The research found that, most of the wellness tourists were in early adulthood. Those wellness tourists found out travel information from online media and from acquaintances. They traveled with family and friends, stayed at hotels and resorts except for Japanese tourists who were mostly elderly rented condominiums for their long-staying. Most of tourists traveled for their own pleasure, aiming to relax and revitalize the body and mind, and to appreciate the beautiful nature and landscape. Activities those attract tourists include: Thai massage, having healthy food and local food, spa, and mineral bath. Most wellness tourists primarily emphasized on safety and quality of food and drink. Wellness tourists needed the provided services with courtesy and humility, also services were supposed to be attentive and enthusiastic, and all the tools and equipment must be cleaned after use.